Stereotactic Re-irradiation for Local Recurrence in the Prostatic Bed After Prostatectomy: Preliminary Results - Olivier, Jonathan; Basson, Laurent; Puech, Philippe; Lacornerie, Thomas; Villers, Arnauld; Wallet, Jennifer; Lartigau, Eric; Pasquier, David (Frontiers in Oncology, 2019)
Objectives: To report the preliminary results of salvage reirradiation in the prostatic bed after radical prostatectomy and salvage external beam radiation therapy (EBRT) using robotic stereotactic body radiation therapy (SBRT) with Cyberknife® for local recurrence of prostate cancer. Materials and methods: Retrospective monocentric analysis was performed on patients treated with SBRT for isolated macroscopic recurrence in the prostatic bed. All patients had radical prostatectomy and salvage or adjuvant EBRT. Local recurrence was documented using magnetic resonance imaging (MRI) and positron emission tomography (PET). Biochemical recurrence was defined as 2 rises in prostate-specific antigen (PSA) of ≥0.2 ng/mL above nadir. Internal gold fiducials were used for the tracking of tumor motion during SBRT. The prescription dose was 36 Gy in 6 fractions for all patients. Toxicity was scored according to the CTCAE v4.0. Results: Between July 2011 and November 2017, 12 patients were treated with SBRT for prostatic bed recurrence with a median follow-up of 34.2 (range, 3.5–64.4) months. Isolated non-metastatic recurrence in the prostatic bed was seen at MRI and PET imaging. Two patients were treated with 6 months androgen deprivation therapy concomitant with reirradiation. The median planning target volume was 4.5 cm3 (range, 1.2–13.3). A PSA decrease after SBRT was found in 10 (83%) patients. The 1-year and 2-years biochemical recurrence-free survival rates were 79% and 56%, respectively. Biochemical recurrence was observed for 6 patients (50%) after a median time of 18 (4–42) months. Toxicity showed: 3 patients (25%) with grade 1 cystitis and 1 patient (8%) with acute grade 2 proctitis at 4 months. One patient (13%) had grade 1 cystitis at 12 months. Conclusion: Reirradiation for local recurrence in the prostatic bed using Cyberknife® after surgery and salvage or adjuvant EBRT is well tolerated and associated with 2-years biochemical recurrence-free survival rates of 56%. Longer follow-up and larger series are necessary.